Developing Worksheet Based on Multiple Intelligences to Optimize the Creative Thinking Students - Luthfiana, Anida; Ambarita, Alben; Suwarjo, Suwarjo (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2018)
The research and development of worksheet based on multiple intelligences aims to develop and describe the effectiveness of worksheet based on Multiple Intelligences to optimizing the ability of creative thinking students. The type of research used is research and development that refers to the theory of Borg & Gall. The population of this research is the students of 5th grade of Primary School in Metro East. The sample of the study was 33 students of 5th grade in Islamic Primary School of Wahdatul Ummah Metro. Data were collected used questionnaires and test questions. The results showed that worksheet based on Multiple Intelligences effectively optimize the creative thinking students.